Two-step thermocompression bonding of High-NA-compatible glass microfluidic chips for imaging flow cytometry - Lingqi Jiang; Yong Han; Lei Gao; Shenglan Yao; Linlin Liu; Wankang Zhai; Jiayi Zhou; Sen Peng; Jingjing Zhao; Zheng You (Journal of Innovative Optical Health Sciences, 2026)
Imaging flow cytometry is rapidly developing toward higher spatial resolution and enhanced capability for resolving subcellular structures, which makes such systems increasingly dependent on high-numerical-aperture objectives for higher-resolution imaging, thereby imposing higher requirements on the stability of three-dimensional hydrodynamic focusing, the quality of optical interfaces, and the structural compatibility of microfluidic chips. In this work, we propose a low-cost fabrication method for glass microfluidic chips for imaging flow cytometry, based on laser processing and a two-step thermocompression bonding strategy. By separating microchannel pre-bonding from overall encapsulation, this method preserves the structural integrity of the microchannels while constructing an optical observation window compatible with high-numerical-aperture objectives, thereby meeting the adaptation requirements of mainstream microscope objectives in terms of working distance and mechanical interfacing. Experimental results show that the optical detection region of the fabricated chip exhibits nanoscale surface quality and good optical transmission performance. Flow imaging experiments further demonstrate that the chip achieved stable three-dimensional hydrodynamic focusing and high-quality fluorescence imaging under high-speed flow conditions, and that the resulting signals exhibited a narrow distribution with low fluctuation, indicating good detection stability and imaging reliability. The study shows that the proposed two-step thermocompression bonding process achieves a balance among the optical performance, structural integrity, and manufacturability of glass microfluidic chips, providing a feasible solution for the fabrication of high-throughput, low-cost, and biosafe chips for imaging flow cytometry.